Effect of Use of a Bougie vs Endotracheal Tube and Stylet on First-Attempt Intubation Success Among Patients With Difficult Airways Undergoing Emergency Intubation: A Randomized Clinical Trial - Driver, Brian E. (JAMA, 2018)
IMPORTANCE: The tracheal tube introducer, known as the bougie, is typically used to aid tracheal intubation in poor laryngoscopic views or after intubation attempts fail. The effect of routine bougie use on first-attempt intubation success is unclear. OBJECTIVE: To compare first attempt intubation success facilitated by the bougie vs the endotracheal tube + stylet. DESIGN, SETTING, AND PATIENTS: The Bougie Use in Emergency Airway Management (BEAM) trial was a randomized clinical trial conducted from September 2016 through August 2017 in the emergency department at Hennepin County Medical Center, an urban, academic department in Minneapolis, Minnesota, where emergency physicians perform all endotracheal intubations. Included patients were 18 years and older who were consecutively admitted to the emergency department and underwent emergency orotracheal intubation with a Macintosh laryngoscope blade for respiratory arrest, difficulty breathing, or airway protection. INTERVENTIONS: Patients were randomly assigned to undergo the initial intubation attempt facilitated by bougie (n = 381) or endotracheal tube + stylet (n = 376). MAIN OUTCOMES AND MEASURES: The primary outcome was first-attempt intubation success in patients with at least 1 difficult airway characteristic (body fluids obscuring the laryngeal view, airway obstruction or edema, obesity, short neck, small mandible, large tongue, facial trauma, or the need for cervical spine immobilization). Secondary outcomes were first-attempt success in all patients, first-attempt intubation success without hypoxemia, first-attempt duration, esophageal intubation, and hypoxemia. RESULTS: Among 757 patients who were randomized (mean age, 46 years; women, 230 [30%]), 757 patients (100%) completed the trial. Among the 380 patients with at least 1 difficult airway characteristic, first-attempt intubation success was higher in the bougie group (96%) than in the endotracheal tube + stylet group (82%) (absolute between-group difference, 14% [95% CI, 8% to 20%]). Among all patients, first-attempt intubation success in the bougie group (98%) was higher than the endotracheal tube + stylet group (87%) (absolute difference, 11% [95% CI, 7% to 14%]). The median duration of the first intubation attempt (38 seconds vs 36 seconds) and the incidence of hypoxemia (13% vs 14%) did not differ significantly between the bougie and endotracheal tube + stylet groups. CONCLUSIONS AND RELEVANCE: In this emergency department, use of a bougie compared with an endotracheal tube + stylet resulted in significantly higher first-attempt intubation success among patients undergoing emergency endotracheal intubation. However, these findings should be considered provisional until the generalizability is assessed in other institutions and settings. TRIAL REGISTRATION: clinicaltrials.gov Identifier: NCT02902146